Digital transformation and the fluid workforce: skill development and capacity building for railway workers - Xiaoxu Yang; Yuming Liu; Jiachen Ji; Kai Liu; Wenjie Li (Journal of Asian Architecture and Building Engineering)
In the context of a globally diverse workforce with varying levels of education and precarious working conditions, this study aims to explore the impact of Social Network Analysis (SNA) on understanding and improving industrial worker skills in railway construction, amid digital transformation challenges. Employing SNA, the research dissects the intricate stakeholder interactions in railway construction projects, identifying 20 critical factors and 10 pivotal connections that significantly influence workforce development and training. The investigation reveals the critical role of digitally-oriented training programs, evolving policy frameworks, and advanced work environments in meeting the sector’s demands. Six strategic directions are introduced, focusing on policy updates, personalized training solutions, and worker well-being initiatives, tailored to navigate the digital transformation challenges effectively. This research provides a novel framework for enhancing worker competencies in the digitally evolving railway construction landscape, integrating SNA with strategic workforce development approaches. The study offers actionable strategies for stakeholders, including government bodies, educational institutions, and industry participants, emphasizing the need for collaboration to implement the proposed interventions. By addressing workforce development comprehensively, the research underscores the importance of technological and policy advancements in fostering a skilled, adaptable, and resilient workforce, contributing to societal progress through improved infrastructure projects.